MORPHOLOGICAL CHARACTERISTICS OF THE EPENDYMAL LAYER OF THE FOURTH VENTRICLE AND THE FIBERS OF THE RADIAL GLIA OF THE MEDULLA OBLONGATA DURING THE PRENATAL PERIOD OF HUMAN ONTOGENESIS - Тихолаз, В.О.; Oniskova, O.V.; Скорук, Р.В.; Шпакова, Н.А.; Ющенко, Л.О. (World of Medicine and Biology, 2018)
Morphological and histological studies of the medulla oblongata in 230 embryos and human fetuses from 6-7 to 39-40 weeks of intrauterine development were performed. Medications of the medulla oblongata stained with hematoxylin-eosin, methylene blue according to Nissl method and immunohistochemically markers (S100, synaptophysin, Ki-67, Bcl-2, vimentin). Computer morphometry and statistical processing of the data were carried out. The different age periods of the changes in the structure and cellular composition of the ependymal layer of the fourth ventricle were determined, the features of the expression of immunohistochemically markers in the cells of the ependymal layer were revealed, and the topography of the fibers of the radial glia of the medulla oblongata in embryos and fetuses of a person of different gestational age was deepened and expanded with respect to the neuroonthogenesis of the central nervous system.